Development of wireless ignition system (WISys) for solid rocket motor - Elexanderio Julit, Iling (2013)
Wireless igniter system (namely WISys in this research) is a modern type igniter system, which utilizes the concept of radio frequency (RF) communication between a transmitting device and a receiving device and also the usage of a specified designated igniter. This type of igniter system is now becoming the main focus in most rocketry industries, especially for small scale solid rocket motor (SRM). The main purpose of using a wireless igniter system is because it can provide secure feeling when conducting experiment and testing, especially when it comes to the matter of explosive materials. The main components that a wireless igniter system must have include a transmitter, a receiver and an igniter. In this research, both the transmitter and receiver were designed to be function able at various ranges and the maximum communication range must reach up to 100 meters. Therefore, selection for wireless communication module is very significant and here the XBee-S1 Starter Kit from Cytron Technologies was used as the main wireless communication module. With its ability to communicate with another XBee-S1 Starter Kit as far as 100 meters range and simplicity of performing configuration and synchronisation, the XBee-S1 Starter Kit module is simply the best choice, especially for those who are unfamiliar with radio frequency communication. Moreover, the power supply for the ignition must be at least 12V so that there is sufficient heating energy to ignite the pyrolant contained inside the igniter within 3 to 5 seconds. For a good igniter, the igniter must possess good characteristics, such as made from stainless steel, sustainable material, high melting point, able to withstand very high pressure and temperature, high resistance to rust, small size and portable, light weight and tough. So, igniter with these characteristics will be able to store enough pressure inside the combustion or primary chamber to achieve complete combustion of the pyrolant before it is forced out from the igniter into the thrust chamber of rocket motor to burn the propellant grains. As a conclusion, with high pressure inside the primary chamber the velocity inside the chamber would be low. Hence, the burning rate of the pyrolant would also be slower. With this condition achieved, the pyrolant inside the igniter could be burnt completely.